2015
DOI: 10.1038/ncb3264
|View full text |Cite
|
Sign up to set email alerts
|

The metabolome regulates the epigenetic landscape during naive-to-primed human embryonic stem cell transition

Abstract: For nearly a century developmental biologists have recognized that cells from embryos can differ in their potential to differentiate into distinct cell types. Recently, it has been recognized that embryonic stem cells derived from both mice and humans display two stable yet epigenetically distinct states of pluripotency, naïve and primed. We now show that nicotinamide-N-methyl transferase (NNMT) and metabolic state regulate pluripotency in hESCs. Specifically, in naïve hESCs NNMT and its enzymatic product 1-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
446
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(482 citation statements)
references
References 71 publications
30
446
5
1
Order By: Relevance
“…Dried samples were stored at −80°C. The LC-MS/MS data were collected by using a standard targeted metabolic profiling MS method in the Northwest Metabolomics Research Center as described (90,91). Briefly, the LC-MS/MS experiments were performed on an Agilent 1260 LC (Agilent Technologies) AB Sciex QTrap 5500 MS (AB Sciex) system.…”
Section: Methodsmentioning
confidence: 99%
“…Dried samples were stored at −80°C. The LC-MS/MS data were collected by using a standard targeted metabolic profiling MS method in the Northwest Metabolomics Research Center as described (90,91). Briefly, the LC-MS/MS experiments were performed on an Agilent 1260 LC (Agilent Technologies) AB Sciex QTrap 5500 MS (AB Sciex) system.…”
Section: Methodsmentioning
confidence: 99%
“…Epigenetic modification by the cellular metabolome has also been shown to regulate the transition from naive to primed PSC states. Naive human PSCs accumulate high levels of nicotinamide N-methyltransferase, which acts to prevent their progression through pluripotency by relieving repressive methylation of WNT via the reduction of S-adenosyl methionine (SAM), a key precursor required by histone methyltransferases (Sperber et al, 2015). Equally, murine naive-to-primed PSC conversion is regulated by the RNA-binding proteins LIN28A and LIN28B, which act to downregulate mitochondrial metabolism and potentiate glycolysis .…”
Section: The Function Of Pi3k/akt/mtor In Regulating Glycolytic Metabmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that cellular metabolism also plays an essential role in regulation of pluripotency, specifically through modulation of the epigenetic landscape (Zhou et al, 2012;Sperber et al, 2015;Zhang et al, 2016). In primed human PSCs, metabolism typically proceeds via the glycolytic pathway, which rapidly switches to oxidative phosphorylation upon differentiation (Zhou et al, 2012;Moussaieff et al, 2015).…”
Section: The Function Of Pi3k/akt/mtor In Regulating Glycolytic Metabmentioning
confidence: 99%
“…Embryonic stem cells share several metabolic features with cancer to maintain their rapid cell cycles and epigenetic landscape necessary for multilineage potency (13)(14)(15). As with stem cells, tumor cells require concerted dysregulation of metabolism and epigenetic cell states to simultaneously accommodate the bioenergetic demands of increased proliferation and aberrant tumor cell fate through epigenetic modification.…”
Section: Introductionmentioning
confidence: 99%